Non-Fragile Projective Synchronization of Fractional-Order Neural Networks with Proportional and Mixed Delays via Memory-Based Sampled-Data Control - Pavithra, G.; Dharani, S. (Discontinuity, Nonlinearity, and Complexity, 2026)
This work delves into the non-fragile projective synchronization (PS) of fractional-order neural networks (FONNs) with proportional and mixed-delay under a memory-based sampled-data (MSD) control framework. We build an MSD controller with norm-bounded uncertainty to accomplish synchronization in the addressed FONN systems. A suitable Lyapunov–Krasovskii functional (LKF) is developed, taking sampling instants into account when mixed delays are present. To provide adequate criteria for the asymptotic stability of the synchronization error system(ES) using linear matrix inequalities (LMIs), the fractional integral inequality is employed. Numerical modeling is provided to present the benefits and applicability of the suggested procedure.